1975
DOI: 10.1071/pp9750501
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Lectins Present in the Tissues of Seed Plants

Abstract: The seeds of both angiosperms and gymnosperms (91 of 104 families tested) contain a specific glycoprotein lectin, which gel-diffusion experiments suggest to be widely present in plant tissues. This lectin will form an insoluble complex with tris-(4-glycosyloxyphenylazo)phloroglucinol where glycosyl = �-D-gluco-, D-galacto-, D-xylo-, malto-, lacto- or cellobiopyranosyl. In legume seeds the major part of the lectin is concentrated in the intercellular spaces as distinct globular bodies. The purification and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(90 citation statements)
references
References 0 publications
1
88
1
Order By: Relevance
“…Although this early survey work was largely based on positive reactivity of plant extracts or tissue sections with Yariv reagent, other tools were subsequently used to confirm that numerous angiosperms, gymnosperms and lower plants (e. g. bryophytes, algae) contain AGPs [29,40,[59][60][61]. …”
Section: Agp Expression In the Plant Kingdommentioning
confidence: 99%
“…Although this early survey work was largely based on positive reactivity of plant extracts or tissue sections with Yariv reagent, other tools were subsequently used to confirm that numerous angiosperms, gymnosperms and lower plants (e. g. bryophytes, algae) contain AGPs [29,40,[59][60][61]. …”
Section: Agp Expression In the Plant Kingdommentioning
confidence: 99%
“…The components of the papillar surface include a fl-glycosyl binding polymer, the "all-fl lectin" described in the seeds of many plants (21). This polymer is apparently identical with a component of the guide mucilaget and is therefore unlikely to be involved in the recognition events, but is more likely to function as a nutrient source and physical support for the developing pollen tube, as well as acting as an adhesive for capturing pollen grains at the stigma surface.…”
Section: Methodsmentioning
confidence: 99%
“…The type II AGPs are a major secretory material found in the medium of cells from all flowering plants grown in liquid culture (Anderson etal., 1977; Aspinall et a/., 1969), but pulsechase studies have shown that they are at least transiently attached to the wall before they are secreted to the medium (Takeuchi and Komamine, 1980). The transient attachment may reflect that soluble AGPs constitute a class of 'p-lectins', a term describing their unique ability to bind specifically to p-linked hexose units (Jermyn and Yeow, 1975). We have proposed that AGPs chaperone some non-cellulosic p-o-glycans to their appropriate extracellular sites of assembly (Carpita and Gibeaut, 1988), but this proposal needs firm data.…”
Section: The Pectin Matrixmentioning
confidence: 99%